Investigation on the drying kinetics of sliced and whole rosehips at different moisture contents under microwave treatment - Evin, Duygu (My University, 2011)
Microwave drying kinetics of rosehips (Rosa Canina L.) harvested at different moisture contents was investigated. The experiments were conducted for both sliced and whole rosehips at different microwave power outputs (90 to 800 W) in a modified microwave drying set-up. Rosehips with initial moisture contents of 0.44 to 0.80 (g water/g dry matter) were dried to moisture content lower than 0.1 (g water/g dry matter). The effects of microwave power level, initial moisture content and slicing on moisture content and drying rate were studied. Drying took place in the falling rate period. To determine the kinetic parameters, drying data were fitted to ten mathematical thin layer drying models. Among the models proposed, Page model precisely represented the microwave drying behavior of rosehip with the coefficient of determination higher than 0.997 and mean square of deviation and root mean square error lower than 4.7×10-4 and 17 ×10-3, respectively for all output powers studied. Values of drying constant (k) were in the range of 0.0049 to 0.23 min-1. © 2011 Academic Journals.
Keywords: Drying kinetics; Microwave drying; Rosehip; Thin layer drying models